Suppose 4*u - 8 = 4. Let l(z) = -z**2 - 10*z - 11. Suppose -4*p - 24 = -p. Let s be l(p). Solve u + 2 = -s*o for o.

-1

Suppose -30*n = -37*n + 28. Solve -4*q = 4 + n for q.

-2

Suppose 0 = p + p - 8. Suppose 0 = 5*j + 2*m + p, m + 4 = j - m. Solve 5*g - g = j for g.

0

Let o(g) be the first derivative of -g**2 - 6*g + 1. Let n = 5 + -10. Let f be o(n). Solve -2*z + f*z = -4 for z.

-2

Let i(t) = -2*t**2 - 18*t - 16. Let o be i(-8). Solve o = -4*m - 1 + 5 for m.

1

Let q be 4/(-10) + 125. Suppose -4*l + 3*k - 3 = 0, 5*l - q*k + k = -1. Solve h + l*h - 2 = 0 for h.

2

Suppose -8 = -4*b + 12. Solve -1 = -2*o + b for o.

3

Let l(o) = -o - 7. Let h be l(-6). Let s be ((-6)/12)/(h/10). Suppose 2*y + 23 = 3*y - 5*t, 2*y = -s*t - 14. Solve 0 = 3*x + 12 + y for x.

-5

Let d(g) = g + 4. Let w be d(-1). Solve -w*f = 1 + 11 for f.

-4

Suppose 0 = 2*d - 6*d. Suppose d = -4*x - 18 - 2. Let q® = r3 + 5*r2 + 2. Let y be q(x). Solve -b + 3 = y*b for b.

1